Exploring physical properties of nanoparticles for biomedical applications - Dani, Raj Kumar (Kansas State University, 2012)
The research work in this thesis aims at investigating the basic physic-chemical properties of magnetic and metal nanoparticles (NPs) for biomedical applications such as magnetic hyperthermia and controlled drug release. Magneto-plasmonic properties of magnetic NPs are important to evaluate potential applications of these materials. Magnetic property can be used to control, monitor and deliver the particles using a magnetic field while plasmonic property allows the tracking of the position of the particles, but aggregation of NPs could pose a problem. Here, the aggregation of NPs is investigated via the Faraday rotation of gold coated Fe[subscript]2O[subscript]3 NPs in alternating magnetic fields. In addition, the Faraday rotation of the particles is measured in pulsed magnetic fields, which can generate stronger magnetic fields than traditional inductive heaters used in the previous experiments. In the second project, the formation of protein-NPs complexes is investigated for hyperthermia treatment. The interactions between gold and iron-platinum NPs with octameric mycobacterial porin A from Mycobacterium smegmatis (MspA) and MspA[superscript])cys protein molecules are examined to assemble a stable, geometrically suitable and amphiphilic proteins-NPs complex. Magnetic NPs show promising heating effects in magnetic hyperthermia to eliminate cancer cells selectively in the presence of alternating magnetic field. As a part of investigation, the heating capacity of a variety of magnetic NPs and the effects of solvent viscosity are investigated to obtain insight into the heating mechanism of these particles. Finally, the controlled drug release of magnetic NPs loaded liposomes by pulsed magnetic field is investigated. The preliminary data indicate about 5-10% release of drug after the application of 2 Tesla magnetic pulses. The preliminary experiments will serve as the initial stage of investigation for more effective magnetic hyperthermia treatment with the help of short magnetic pulses.
Keywords: Magnetic hyperthermia; Drug release; Faraday Rotation; Magnetic nanoparticles; Cancer treatment; Magnetoliposomes; Chemistry (0485); Oncology (0992); Physical Chemistry (0494)